Exploring how 3D printing parameters affect the flexural strength of ABS materials - Diki Anggara; Rifelino Rifelino; Zainal Abadi; Andril Arafat (Innovation in Engineering, 2024)
This research focuses on testing the flexural strength of Acrylonitrile Butadiene Styrene (ABS) materials used in 3D printing by the Fused Deposition Modeling (FDM) method. The objective of this study was to evaluate the mechanical strength of ABS using a full factorial experimental design, applying three main factors such as layer height, infill density and infill pattern. Flexural testing was conducted following ASTM D790 standards. A total of 27 specimens were made by varying the layer height, infill density and infill pattern. The results showed that layer height was the most influential factor on flexural strength, with the highest value of 41.815 Mpa at 0.2 mm layer height, 100% infill density, and line infill pattern. ANOVA analysis supported this conclusion with p values <0.05 for layer height, while infill pattern and infill density showed no significant effect. This study provides guidelines for the use of optimal parameters in ABS-based 3D printing processes.